The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/6653593
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Calcium Oxalate Formation and Antioxidant Activity of Carboxymethylated Poria cocos Polysaccharides

Abstract: Three carboxymethylated Poria cocos polysaccharides (PCP-C1, PCP-C2, and PCP-C3) with -COOH contents of 6.13%, 10.24%, and 16.22%, respectively, were obtained by carboxymethylation of the original polysaccharide (PCP-C0), which has a molecular weight of 4 kDa and a carboxyl (-COOH) content of 2.54%. The structure of the PCP-Cs was characterized by FT-IR, 1H NMR, and 13C NMR spectra. The four PCP-Cs exhibited antioxidant activity, and their ability to scavenge radicals (hydroxyl and DPPH) and chelate ferrous io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…The higher the degree of carboxymethylation, the higher the carboxyl content and the better the performance of the antioxidant activity. 49 Our previous studies 26 showed that corn silk polysaccharide showed the strongest antioxidant activity when its molecular weight was 6.0 kDa (in the range of 2.0−124 kDa), and it could inhibit the transformation of calcium oxalate dihydrate (COD) crystals into calcium oxalate monohydrate (COM) crystals. In this study, the performance of corn silk polysaccharide is similar to that of Poria cocos polysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the degree of carboxymethylation, the higher the carboxyl content and the better the performance of the antioxidant activity. 49 Our previous studies 26 showed that corn silk polysaccharide showed the strongest antioxidant activity when its molecular weight was 6.0 kDa (in the range of 2.0−124 kDa), and it could inhibit the transformation of calcium oxalate dihydrate (COD) crystals into calcium oxalate monohydrate (COM) crystals. In this study, the performance of corn silk polysaccharide is similar to that of Poria cocos polysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…Henceforth, the chelating influence on ferrous ions has been lately broadly used to assess some antioxidant activity of polysaccharides (Huang et al 2021 ). The iron-chelating ability of polysaccharides may be associated with the formation of cross-bridges between the carboxyl group in uronic acid and the divalent ions (Li et al 2021 ). The chelating rate of a novel heteropolysaccharide obtained from A. pubescens root was close to our present investigation at 2.0 mg mL −1 (Yuan et al 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…After carboxymethylation, the molecular weight of polysaccharide from Cyclocarya paliurus decreased and correspondingly the molar ratio of monosaccharide composition changed ( 144 ). Among carboxymethylated polysaccharides, the antioxidant activity aims to terminate free radicals against oxidation reactions from occurring by increasing the ability of chelating transition metal ions and providing single electron or hydrogen atoms with the increased content of -COOH ( 145 ). It is worth mentioning that there is a positive correlation between antioxidant activity and the degree of carboxymethylation within a certain range ( 146 ).…”
Section: Structural Modificationmentioning
confidence: 99%